Apartment 7A [videorecording (DVD)] - James, Natalie Erika; White, Christian; James, Skylar; Garner, Julia, 1994-; Sturgess, Jim; Wiest, Dianne; McNally, Kevin; Buchan, Andrew, 1979-; Siu, Marli, 1993-; McEwen, Rosy; Holdbrook-Smith, Kobna; Valls Colomer, Arnau, 1978-; et al. (Paramount, 2024)
New York City, 1965. What happened in the apartment before Rosemary moved in? A struggling dancer finds herself drawn into dark forces by a peculiar couple promising her fame.